Panorama of the Intracellular Molecular Concert Orchestrated by Actinoporins, Pore-Forming Toxins from Sea Anemones - Alvarez Valcárcel, Carlos M (2021)
Actinoporins (APs) are soluble pore-forming proteins secreted by sea anemones that experience conformational changes originating in pores in the membranes that can lead to cell death. The processes involved in the binding and pore-formation of members of this protein family have been deeply examined in recent years; however, the intracellular responses to APs are only beginning to be understood. Unlike pore formers of bacterial origin, whose intracellular impact has been studied in more detail, currently, we only have knowledge of a few poorly integrated elements of the APs’ intracellular action. In this review, we present and discuss an updated landscape of the studies aimed at understanding the intracellular pathways triggered in response to APs attack with particular reference to sticholysin II, the most active isoform produced by the Caribbean Sea anemone Stichodactyla helianthus. To achieve this, we first describe the major alterations these cytolysins elicit on simpler cells, such as non-nucleated mammalian erythrocytes, and then onto more complex eukaryotic cells, including tumor cells. This understanding has provided the basis for the development of novel applications of sticholysins such as the construction of immunotoxins directed against undesirable cells, such as tumor cells, and the design of a cancer vaccine platform. These are among the most interesting potential uses for the members of this toxin family that have been carried out in our laboratory.